2019
DOI: 10.1038/s41467-019-08642-y
|View full text |Cite
|
Sign up to set email alerts
|

Redox gated polymer memristive processing memory unit

Abstract: Memristors with enormous storage capacity and superior processing efficiency are of critical importance to overcome the Moore’s Law limitation and von Neumann bottleneck problems in the big data and artificial intelligence era. In particular, the integration of multifunctionalities into a single memristor promises an essential strategy of obtaining a high-performance electronic device that satisfies the nowadays increasing demands of data storage and processing. In this contribution, we report a proof-of-conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 63 publications
0
97
0
Order By: Relevance
“…The oxidation is reversible, with most of the charged PQT along the SD line reduced back to neutral PQT upon reversal of the bias to V SG = −2 V. This observation provides a direct correlation of polaron generation with device conductivity. Zhang et al [77] investigated the spatial evolution of the oxidative states of the ferrocene pendant triphenylamine (TPA) and ferrocene (Fc) (PFTPA-Fc) thin film under different applied voltages through fluorescence line scans. Strong emission appeared in the wavelength range of 410-460 nm in initial state with emissions between 430 and 460 nm and between 415 and 430 nm corresponding to Fc and TPA, respectively (Figure 9c).…”
Section: Switching Mechanisms In Organic Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxidation is reversible, with most of the charged PQT along the SD line reduced back to neutral PQT upon reversal of the bias to V SG = −2 V. This observation provides a direct correlation of polaron generation with device conductivity. Zhang et al [77] investigated the spatial evolution of the oxidative states of the ferrocene pendant triphenylamine (TPA) and ferrocene (Fc) (PFTPA-Fc) thin film under different applied voltages through fluorescence line scans. Strong emission appeared in the wavelength range of 410-460 nm in initial state with emissions between 430 and 460 nm and between 415 and 430 nm corresponding to Fc and TPA, respectively (Figure 9c).…”
Section: Switching Mechanisms In Organic Devicesmentioning
confidence: 99%
“…Not like showing in the Pt/Ta 2 O 5 /Pt device (Figure 11f), Ta metal can be oxidized spontaneously, which can produce a hazy interface between the cathode and Ta 2 O 5 film as a load resistor to inhibit the overgrowth of nanofilaments. Furthermore, Xue et al [77] found the forming voltages of the switching devices strongly depend on the roughness of the interface between electrode and switching layer. The smaller forming voltage/free forming process can be obtained in memristors with rougher interface (Figure 11h) [77].…”
Section: Interface Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The high resistance state (HRS) can be regarded as “0” bit in data storage, and thus the switching from HRS to the low resistance state (LRS) is equivalent to “0”‐to‐“1” binary conversion. Based on this concept, multibit storage (eg, “0,” “1,” “2”) can be expected when more than two resistance states of one material are acquired under the electric field, 16‐18 which contributes to exponentially increase the storage capacity within one memory cell.…”
Section: Introductionmentioning
confidence: 99%
“…Proposals for computers that exploit chemical processes have taken one or both of two broad approaches: 1) using chemistry and biochemistry to emulate circuit components or cellular automata, and 2) employing a large number of molecules to explore a combinatorial space in parallel. Examples for the first include reaction-diffusion systems (7), Belousov-Zhabotinsky oscillatory reaction (8), memristive polymers (9), and transcription regulation for cellular signaling (10,11), and other chemical and biochemical analogues of logic gates (12,13). In the second category of parallelized computing, we find microfluidic devices (14), nanofabricated networks (15)(16)(17), and adaptive amoebal networks (18).…”
Section: Introductionmentioning
confidence: 99%